Вплив змін облікової політики підприємства на фінансову звітність за МСФЗ - Шматова, Валерія Олександрівна; Якименко-Терещенко, Наталія Василівна (My University, 2019)
У статті розглянуто вплив елементів облікової політики у разі її зміни на фінансовий результат діяльності підприємства. Розкрито сутність поняття "облікова політика", головне її призначення. Розглянуті нормативно-правові акти, за допомогою яких формується облікова політика підприємства. Визначено значення облікової політики підприємства для користувача. Окреслено елементи, які найбільше впливають на фінансові результати. Визначено вплив обліку основних засобів, а саме строків корисного використання, на показники фінансової звітності. Сформульовано підхід до капіталізації ремонтів на підприємстві. Проаналізовано процес та облік капіталізації процентних витрат та курсових різниць. Розглянуто облік об’єктів, що не використовуються в діяльності, та облік витрат, що мають довгостроковий (інвестиційний) характер. Визначено підхід до створення оціночних значень. Проаналізовано наявні методи розглянутих елементів облікової політики.

The main objective of the financial and economic activities of any commercial enterprise is to make a profit. Profit is a positive financial result of the organization. Each organization is interested in obtaining the highest possible financial result, and in connection with this, the organization has the goal of optimizing profit while strengthening the financial condition. In many respects, a well-formed accounting policy allows optimizing the profit margin, which makes it possible to better present the financial situation of an economic entity and its financial result due to the choice of methodological techniques. The work is devoted to the study of issues on the formation and use in accounting, such an important internal document as the accounting policy of the enterprise. The relevance of this topic lies in the fact that in modern economic conditions, with frequently changing legislation, accounting is oriented towards international accounting and reporting standards, while accounting policies provide an opportunity for a legal way to decide all disputed issues. The need to study the issues of essence and the formation of accounting policies and its implementation in practice determined the choice of this topic of the article. The article examined the influence of elements of accounting policies when they change on the financial result of the enterprise. The purpose of the article is to determine the theoretical provisions of accounting policies and the impact of its changes on the financial statements in the application of international financial reporting standards. The essence of the concept of “accounting policy”, its main purpose is disclosed. The regulatory legal acts with the help of which the accounting policy of the enterprise is formed are considered. The value of the enterprise accounting policy for the user is determined. Highlighted elements that have the greatest impact on financial results. The impact of accounting for fixed assets, namely useful lives, on the financial statements is determined. The approach to capitalization of repairs at the enterprise is formulated. The process and accounting of capitalization of interest expenses and exchange rate differences are analyzed. Considered the accounting of objects that are not used in activities and cost accounting, are long-term (investment) in nature. The approach to creating estimated values is defined. The existing methods of the considered elements of accounting policies are analyzed.
Impact of changes in an entity's accounting policies on IFRS financial statements
Keywords: облікова політика; фінансовий результат; користувачі облікової політики; методи обліку; accounting policy; financial result; users of accounting policies; accounting methods